2021
DOI: 10.3389/fnins.2021.628836
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Framework for Insomnia: A Cognitive Model in Practice

Abstract: Insomnia is a widespread neuropsychological sleep-related disorder known to result in various predicaments including cognitive impairments, emotional distress, negative thoughts, and perceived sleep insufficiency besides affecting the incidence and aggravation of other medical disorders. Despite the available insomnia-related theoretical cognitive models, clinical studies, and related guidelines, an evidence-based conceptual framework for a personalized approach to insomnia seems to be lacking. This study prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 81 publications
(94 reference statements)
0
13
0
Order By: Relevance
“…Figure 1 shows the proportion of participants who had an insomnia disorder (ISI ≥ 8) and categorized the level of insomnia disorder, including the absence of insomnia (0-7), mild insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). There was approximately one-third of respondents who had insomnia symptoms (34.5%) categorized as mild, moderate or severe symptoms of insomnia, which were recorded as 18.2%, 12.6% and 3.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Figure 1 shows the proportion of participants who had an insomnia disorder (ISI ≥ 8) and categorized the level of insomnia disorder, including the absence of insomnia (0-7), mild insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). There was approximately one-third of respondents who had insomnia symptoms (34.5%) categorized as mild, moderate or severe symptoms of insomnia, which were recorded as 18.2%, 12.6% and 3.7%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The cut-off score for diagnosing insomnia disorder is ≥8 while the absence of insomnia scored in the range from 0 to 7. 26 The total score of insomnia disorder is categorized as follows; mild insomnia (8)(9)(10)(11)(12)(13)(14), moderate insomnia (15)(16)(17)(18)(19)(20)(21), and severe insomnia (22)(23)(24)(25)(26)(27)(28). 27…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another systematic review [6] that included information from 32 countries showed that there was an increase in the prevalence of mental health issues in the general population during the COVID-19 pandemic, with estimated global prevalence of depression, anxiety, and sleep problems of 27% to 28%, indicating that social and economic burdens during and after epidemics or pandemics have a great global impact. Among these frequent symptoms of long COVID, insomnia has recently been recognized as a neuropsychological disorder leading to various medical issues including cognitive impairments, emotional distress, negative thoughts, and further medical disorders [7]. In addition, sleep disturbance has been reported in various populations, not only in the acute phase of infection, but also in the chronic phase after recovery from acute symptoms [8].…”
Section: Introductionmentioning
confidence: 99%
“…The neurocognitive approach has opened new avenues for research and innovation in clinical practice. Clinical utilities were revealed in recent studies about neurocognitive evaluation in the differential diagnosis (HALE et al, 2011;WEISSMAN et al, 2012), the cognitive-behavioral efficacy (KUELZ et al, 2006;LEGERSTEE et al, 2010;MATHEWS et al, 1995;GORMAN, 2005;THASE, 2006), pharmacological (HALE; FIORELLO; BROWN, 2005;HALE et al, 2011), and neurocognitive rehabilitation (KERNS; ESO; THOM-SON, 1999;KOSTER;FOX;MACLEOD, 2009;VASSILOPOULOS;PRANTZA-LOU, 2009)in affective disorders and cognitive impairments GHODRATITOOSTANI et al, 2016a;TOOSTANI et al, 2017;VAZIRI et al, 2021). Another compelling reason for adopting a neurocognitive perspective is recognizing and measuring the severity of symptoms, syndromes, and disorders.…”
Section: Introductionmentioning
confidence: 99%